2007
DOI: 10.1093/geront/47.6.798
|View full text |Cite
|
Sign up to set email alerts
|

Grief and Personal Growth Experience of Spouses and Adult-Child Caregivers of Individuals With Alzheimer's Disease and Related Dementias

Abstract: Purpose: The purpose of this study was to describe the grief and personal growth experience of spouses and adult children of individuals with Alzheimer's disease and related dementias and the factors contributing to these experiences. Design and Methods: We used a modification of the MarwitMeuser-Sanders Caregiver Grief model to examine the factors that contribute to grief and personal growth. We used chi-square tests, t tests, multivariate analyses of variance, correlations, and hierarchical regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
120
2
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(146 citation statements)
references
References 48 publications
17
120
2
7
Order By: Relevance
“…In contrast, spousal carers, particularly wives, tended to place a higher value on gains based in the dynamic of their relationship and on spiritual growth. These differences support previous research (Ott, Sanders & Kelber, 2007) and may reflect the different times of life that these carers embark on their caregiving journey. Adult child carers tend to be younger and therefore may have had less opportunity for personal development than older spousal carers.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, spousal carers, particularly wives, tended to place a higher value on gains based in the dynamic of their relationship and on spiritual growth. These differences support previous research (Ott, Sanders & Kelber, 2007) and may reflect the different times of life that these carers embark on their caregiving journey. Adult child carers tend to be younger and therefore may have had less opportunity for personal development than older spousal carers.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, they would have to combine the care tasks with other obligations (such as family and work) and this could more easily lead to a clash of responsibilities and greater burden. As stated by other authors [40][41][42] the feelings of guilt reported by adult child caregivers, which also have negative repercussions for patients, could be associated with the difficulties that caregivers face in providing the best possible care for their parents or the emotional distance they feel with respect to them.…”
Section: Differences In Perceived Qol-p Between Spouse and Adult Chilmentioning
confidence: 83%
“…Social isolation has been reported to be more common among spouses than adult children, with the latter being more involved in various activities and settings (Rinaldi et al, 2005;Ott et al, 2007;Sanders et al, 2008).…”
Section: Empirical Researchmentioning
confidence: 99%
“…In contrast, spouse caregivers have greater experience of caring (Sörensen et al, 2002) and take more advantage of peer support (Lavoie et al, 2005), being more assiduous in their attendance at support groups (Ott et al, 2007).…”
Section: Empirical Researchmentioning
confidence: 99%
See 1 more Smart Citation